Experimental AI Lab in Journalism and Communication - Skovbjerg, Annegrete; Larsen, Inger Knude; Bækgaard, Michael (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
In this project we are investigating how generative artificial intelligence (GAI) can be didactically integrated into teaching with the goal to strengthen students' AI literacy. The focal point is creating an AI lab in the form of a scenario-based game, where journalism and communication students use AI tools collaboratively to produce content in a realistic scenario. Students must produce content using GAI programmes in the scenario. After the game they must reflect on the AI tools' relevance and ethical implications in the scenario and the profession as such. The students’ experiences and critical reflections are essential in the project. We also examine how we as educators can design the AI lab using GAI tools. In the making of the scenario and the tasks in the game, we have used ChatGPT and Midjourney to develop specific roles and situations of conflict during the game. The Gamemaster has also used ChatGPT during the games to develop the tasks for the groups. This makes the development of the scenario flexible and enables turning the story and the tasks in different directions. The project is grounded in Reflective Practice-based Learning (RPL) and follows a Design-Based Research (DBR) approach.